Lipemic index a tool to measure lipemia - Usha Adiga; B. N Malawadi (International Journal of Medical Research and Review, 2016)
Introduction: Lipemia is represented as turbidity in the serum or plasma which becomes evident before the analytical process. It is mainly caused by large particles of lipoproteins such as chylomicrons or VLDL, the main lipid component of which is triglyceride. Lipemic interference is commonly found in routine clinical chemistry tests. It can, not only influence measurements of analytes, but can also cause false increase or decrease intheir levels. The aim was to use Lipemic index (LI) as an automated determinant of lipemia in venous blood specimens sent to our clinical chemistry laboratory and measure the extent of turbidity.Methods: The study was conducted in Clinical Biochemistry laboratory in the month of January 2016.Total of 809 samples were collected and lipemic index (LI) was estimated in autoanalyzer, transasia XL-640.LI values were categorized from L- to L++++.Percentage of sample in each category was calculated.Results: Most of our patients (68.23%) had LI <10,that is L-.A considerable group (28.3%) were in L+ range. Highest degree of lipemia was observed in 0.98% patients. Females had less turbid samples as compared to men. A greater proportion of women (58.7%) had LI <10 as compared to men (41.3%).From L+ to L++++ ,men had higher LI as compared to women.Conclusion: Lipemic index estimation ensures that the sample is fit for analysis. The use of automated LI estimation overcomes the limitations associated with visual estimation by providing a more objective and accurate estimate of lipemia.